The assessment and management of chronic cough in children according to the British Thoracic Society guidelines: descriptive, prospective, clinical trial. (10th February 2014) - Usta Guc, Belgin; Asilsoy, Suna; Durmaz, Cemile
Abstract Background Chronic cough is a common problem of various etiologies. While diagnosis may relatively be easy in the presence of some specific findings, it tends to be rather difficult when there are no clear symptoms. Therefore, practical guidelines are needed for management of patients with chronic cough. We aimed to evaluate assessment and management of chronic cough in children according to the British Thoracic Society guidelines published in 2008. Methods Patients with chronic cough lasting longer than 8 weeks between 5 and 16 years old were evaluated. Pulmonary function test and chest radiography were performed on all patients. Further workup was conducted on those requiring further investigation. Patients were re‐evaluated at 2‐ to 4‐week intervals, and we followed our patients for 18 months until cough resolved. Results One hundred fifty six patients (52.5% female) aged 5–16 (8.42 ± 2.6) years were included. Of the 156 patients, 19.2% (n = 30) were diagnosed with postnasal drip syndrome plus asthma; 18.6% (n = 29) with postnasal drip syndrome; 12.2% (n = 19) with asthma; 12.2% (n = 19) with protracted bacterial bronchitis; and 11.5% (n = 18) with nonspecific isolated cough, 9.6% (n = 15) with cough variant asthma, 5.7% (n = 9) with psychogenic cough and 3.2% (n = 5) with gastroesophageal reflux disease. Conclusions Postnasal drip syndrome and asthma was the most common cause of chronic cough. Asthma‐associated findings were found in some of the patients diagnosed with postnasal drip syndrome. It has been observed that there could be more than one particular cause for cough concerning some patients. The gastroesophageal reflux disease was not a common primary cause of chronic cough in children.